ANALISIS ANTESEDAN MINAT MENABUNG DI PT BANK MANDIRI CABANG SANGATTA - Limber Marampa; Pradopo; Efendi Rahmanto (Tinta Nusantara 2018 Vol.1, 2022)
The purpose of this study was to determine the effect of product quality, promotion and location at PT Bank Mandiri (Tbk) Sangatta Branch on interest in saving. This study uses field research with a quantitative approach which is carried out by distributing questionnaires to 100 respondents who are saving customers at PT Bank Mandiri (Tbk) Sangatta Branch, using validity and reliability test analysis techniques, classical assumption test, multiple regression equation, t test, d test and coefficient of determination processed with the SPSS version 21 application. Based on the results of the study, it was found that product quality was a significant variable and had a positive effect on increasing customer interest in saving. Meanwhile, promotion does not have a significant or negative effect on customer interest in saving. Meanwhile, location is also a variable that has a significant or positive effect on customer interest in saving.